IMPLEMENTASI MEDIA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTs HASYIM ASY’ARI KOTA BATU. - Ersa Aprilia Pradani; Nur Hasan; Bahroin Budiya (VICRATINA, 2022)
Audio visual based learning media is a learning media that looks, can be heard, can also be used to convey massage or also subject matter in more detail and clearly, from the learning that is displayed on audio visual media it can be heard as well as seen, learning using audio visual media is a form of conveying material by using machines or mechanical and electronic devices to display or present audio and visual massage. Then what is meant by implementation is the provision of facilities to carry out something that has a certain impact, or simply implementation. This research was conducted at one of the Madrasah Tsanawiyah education in Batu City. The purpose of this study is to find out how the implementation of audio visual media in the learning process of Islamic Cultural History based on audio visual media at MTs Hasyim Asy’ariBatu City, also to find out how the learning model is when the learning process takes place. The approach used in this research is qualitative research. There are three data collection techniques in this research, namely: 1) Observation, 2) Interview, 3) Documentation. The subject in this study were grade VIII students in the 2021/2022 academic year.It can be concluded from the data obtained by the researcher, namely, during the learning process,it was seen that students could more easily understand the material being taught, were more enthusiastic in the learning process, and the learning model used by the VIII grade SKI teacher was the direct and cooperative learning model. First, the direct learning model is where the teacher explains the learning video in class directly, then explains the content of the material. The second model is the cooperative learning model, whwre the teacher forms small groups then the teacher gives assignments, and then presents them in front of the class.